Scrodentoid A Inhibits Mast Cell–Mediated Allergic Response by Blocking the Lyn–FcεRIβ Interaction - Qian, Fei; Zhang, Liuqiang; Lu, Shaodong; Mao, Gaohui; Guo, Fujiang; Liu, Ping; Xu, Jinwen; Li, Yiming (Frontiers in Immunology, 2019)
Background: Mast cells are considered an attractive therapeutic target for treating allergic diseases, and the Lyn–FcεRIβ interaction is essential for mast cell activation. This study investigated the antiallergic effect of scrodentoid A (SA) on mast cells and mast cell–mediated anaphylaxis. Methods: For in vitro experiments, mast cells were treated with SA. Cell proliferation was tested using the XTT assay. The mRNA expression of various cytokines and chemokines was measured using qPCR. The levels of histamine, eicosanoids (PGD2, LTC4), and cytokines were measured using enzyme immunoassay kits. Signaling was investigated using Western blotting and immunoprecipitation. For in vivo experiments, the antiallergic activity of SA was evaluated using two mouse models of passive anaphylaxis as passive cutaneous and systemic anaphylaxis. The mechanism was investigated through immunohistochemistry and immunofluorescence. Results: SA considerably inhibited immunoglobulin (Ig) E-mediated mast cell activation, including -hexosaminidase release, mRNA and protein expression of various cytokines, and PGD2 and LTC4 release. Oral administration of SA effectively and dose-dependently suppressed mast cell–mediated passive cutaneous and systemic anaphylaxis. SA significantly attenuated the activation of Lyn, Syk, LAT, PLCγ, JNK, Erk1/2, and Ca2+ mobilization without Fyn, Akt, and P38 activation by blocking the Lyn–FcεRIβ interaction. Conclusions: SA suppresses mast cell–mediated allergic response by blocking the Lyn–FcεRIβ interaction in vitro and in vivo. SA may be a promising therapeutic agent for allergic and other mast cell–related diseases.